Medical Negligence By Doctors Resulting in Criminal Law Charges (Case Study on the Decision of the Supreme Court of the Republic of Indonesia No. 590 K/PID/2012) - Keristian, Hendrik Rejeki; Triana, Yeni (Journal of Community Health Provision, 2025)
This study investigates the legal consequences of medical negligence in Indonesia, focusing on Supreme Court Decision No. 590 K/Pid/2012 involving Dr. Wida Parama Astiti. The case centers on the death of a pediatric patient following the unsupervised administration of potassium chloride (KCl), a high-alert medication, in violation of national safety protocols. The research adopts a normative juridical approach, examining relevant statutory frameworks including Article 51 of Law No. 29 of 2004 concerning Medical Practice, Minister of Health Regulation No. 11 of 2017 on Patient Safety, and Articles 359 and 361 of the Indonesian Criminal Code. The analysis explores the application of the legal concept of culpa (negligence), particularly culpa lata (gross negligence), to determine the criminal liability of the defendant. Findings show that the failure to follow mandated medical protocols and provide direct supervision constituted a breach of professional duty, justifying the court’s custodial sentence. The study also highlights the role of systemic shortcomings in patient safety enforcement within hospital settings. This case serves as a critical reference for understanding how Indonesian law addresses gross medical negligence, setting a precedent for future litigation involving healthcare professionals. The research contributes to legal scholarship by clarifying the boundaries of professional accountability and emphasizing the need for institutional safeguards. It also provides practical recommendations for enhancing regulatory compliance and protecting patient rights through stricter enforcement of medical standards.